Prevalence and Distribution of Potentially Human Pathogenic Vibrio spp. on German North and Baltic Sea Coasts - Fleischmann, Susanne; Herrig, Ilona; Wesp, Jessica; Stiedl, Joscha; Reifferscheid, Georg; Strauch, Eckhard; Alter, Thomas; Brennholt, Nicole (Frontiers in Cellular and Infection Microbiology, 2022)
Global ocean warming results in an increase of infectious diseases including an elevated emergence of Vibrio spp. in Northern Europe. The European Centre for Disease Prevention and Control reported annual periods of high to very high risks of infection with Vibrio spp. during summer months along the German coasts. Therefore, the risk of Vibrio infections associated with recreational bathing in European coastal waters increases. To obtain an overview of the seasonal and spatial distribution of potentially human pathogenic Vibrio spp. at German coasts, this study monitored V. cholerae, V. parahaemolyticus and V. vulnificus at seven recreational bathing areas from 2017 to 2018, including heat wave event in summer 2018. The study shows that all three Vibrio species occurred in water and sediment samples at all sampling sites. Temperature was shown to be the main driving factor of Vibrio abundance, whereas Vibrio community composition was mainly modulated by salinity. A species-specific rapid increase was observed at water temperatures above 10°C, reaching the highest detection numbers during heat wave event with abundances of 4.5 log10 CFU+1/100ml seawater and 6.5 log10 CFU+1/100g sediment. Due to salinity, the dominant Vibrio species found in North Sea samples was V. parahaemolyticus, whereas V. vulnificus was predominantly detected in Baltic Sea samples. Most detections of V. cholerae were associated with estuarine samples from both seas. Vibrio spp. concentrations in sediments were up to three log higher compared to water samples, indicating that sediments are an important habitat for Vibrio spp. to persist in the environment. Antibiotic resistances were found against beta-lactam antibiotics (Ampicillin 31%, Cefazolin 36%, Oxacillin and Penicillin 100%) and trimethoprim-sulfamethoxazole (45%). Moreover, isolates harbouring pathogenicity associated genes such as trh for V. parahaemolyticus as well as vcg, cap/wcv and the 16S rRNA-typeB variant for V. vulnificus were detected. All sampled V. cholerae isolates were identified as non-toxigenic non-O1/non-O139 serotypes. To sum up, increasing water temperatures at German North Sea and Baltic Sea coasts provoke elevated Vibrio numbers and encourages human recreational water activities resulting in increased exposure rates. Owing to a moderate Baltic Sea salinity, the risk of V. vulnificus infections is of particular concern.